2011
DOI: 10.1177/1091581810397774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anesthetics and Terminal Procedures on Biochemical and Hormonal Measurements in Polychlorinated Biphenyl Treated Rats

Abstract: This investigation reports the effects of various terminal procedures, and how they modified the responses to a toxicant (polychlorinated biphenyls [A1254], 130 mg/kg/day × 5 days) administered by gavage to Sprague-Dawley male rats. Terminal procedures included exsanguination via the abdominal aorta under anesthesia (isoflurane inhalation or Equithesin injection), decapitation with or without anesthesia, or narcosis induced by carbon dioxide inhalation. Effects of repeated anesthesia were also tested. Terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
3
6
0
Order By: Relevance
“…The data demonstrate that isoflurane elevated plasma corticosterone levels of female, but not male, rats. Our findings are consistent with those of several other studies using male rats which have reported no changes in corticosterone levels following similar exposures to isoflurane [2, 11, 12]. A substantial body of literature shows that female rats display greater HPA axis activity including higher corticosterone levels compared to males at both baseline and in reaction to an acute stressor [1315].…”
Section: Discussionsupporting
confidence: 92%
“…The data demonstrate that isoflurane elevated plasma corticosterone levels of female, but not male, rats. Our findings are consistent with those of several other studies using male rats which have reported no changes in corticosterone levels following similar exposures to isoflurane [2, 11, 12]. A substantial body of literature shows that female rats display greater HPA axis activity including higher corticosterone levels compared to males at both baseline and in reaction to an acute stressor [1315].…”
Section: Discussionsupporting
confidence: 92%
“…The levels of glucose at baseline (time 0) were already quite elevated. This was most probably due to the use of an anaesthetic (isoflurane), which induces blood glucose level elevation, as has been reported previously ( 21 , 22 ) . The levels of insulin and glucose following 45 E% diet feeding for 12 weeks indicated that the mice were developing hyperglycaemia or insulin sensitivity reduction, as fasting blood glucose and insulin levels were elevated when compared with those in mice fed the 10 E% diet.…”
Section: Resultssupporting
confidence: 66%
“…Although these data indicate a potential problem with TH feedback on the PVN, the expression of thyroid receptor-β (THRβ), which is a key receptor involved in TH feedback on the PVN, was not observed to be altered (data not shown). Reports have also indicated that isoflurane anesthesia may decrease peripheral T4 levels in adult male rats [37], but given the short span of time between anesthesia and blood collection in the adult rats in our study, it is unlikely that this explains the inconsistent TH results between juvenile and adult rats. Finally, peripheral TH levels may not reflect the non-neuroendocrine effects mediated by TRH, suggesting that local signaling by this peptide within the brain may be influencing CBT and other metabolic processes.…”
Section: Discussionmentioning
confidence: 67%